2023
DOI: 10.1109/access.2023.3266156
|View full text |Cite
|
Sign up to set email alerts
|

Secure IoMT for Disease Prediction Empowered With Transfer Learning in Healthcare 5.0, the Concept and Case Study

Abstract: Identifying human diseases remains a difficult process, even in the age of advanced information technology and the smart healthcare industry 5.0. In the smart healthcare industry 5.0, precise prediction of human diseases, particularly lethal cancer diseases, is critical for human well-being. The global Internet of Medical Things sector has advanced at a breakneck pace in recent years, from small wristwatches to large aircraft. The critical aspects of the Internet of Medical Things include security and privacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Using a variety of metrics will significantly help in defining the performance of this model [35]. The equations of the previously mentioned measures are [36][37][38]:…”
Section: Performance Measurementioning
confidence: 99%
“…Using a variety of metrics will significantly help in defining the performance of this model [35]. The equations of the previously mentioned measures are [36][37][38]:…”
Section: Performance Measurementioning
confidence: 99%
“…In contrast to the studies in the literature, the proposed study investigated a middle eastern dataset while addressing the kingdom's waste management problem, which is first of its kind study in the kingdom. ResNEt34, VGG126, InceptionV3, DenseNet121, MobileNetV3, and GNet [43] 24,000 images from Huawei challenge cup dataset [24] GNet accuracy = 92.62% [33] YoloV5 [45] TrashNet Accuracy = 95.51% [37] CNN [44] TrashNet Accuracy = 92.6% [38] InceptionV3 [43] TrashNet Accuracy = 92.87% [14] EfficientdetD2 & EfficientnetB2 [43] 14,000 instances Accuracy = 75% [21] MLH-CNN, AlexNet, RestNet50, and VGG16, DL model with (DLSODC-GWM) [43] Benchmark datasets Precision = 95.23%, Recall = 94.29% F-score = 94.73% [28] CNN [44] TrashNet, and self-built dataset Accuracy = 96.77% [32] GCNet [43] Internet collected dataset combined with self-built dataset Accuracy = 97.54%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several deep learning models were investigated, and it was concluded that the proposed CNN model outperformed the other models with the highest accuracy of 99.82%. In transfer learning, the knowledge gained from a pretrained model is used as a starting point for training a new model, rather than starting from scratch [26][27][28].…”
Section: Classification Using Deep Learningmentioning
confidence: 99%
“…It can help improve the performance of a model by leveraging the knowledge gained from a pretrained model. Moreover, it can improve the generalization performance of a model, and it allows the model to learn from a larger and more diverse set of data [26][27][28]. In the context of plants, taxonomy involves classifying plants into different groups based on their morphological, physiological, and molecular characteristics.…”
Section: Proposed Transfer Learning Approachmentioning
confidence: 99%